Faktor-Faktor yang Mempengaruhi Efektifitas Praktik Laboratorium Daring Pada Masa Pandemi Covid-19 - Nurhalimah Nurhalimah; Deby Fitriayuningsih; Omi Haryati; Dwi Kartika Rahayuningtyas (Jurnal Keperawatan, 2021)
The teaching and learning process during the Covid-19 pandemic underwent a change, previouslyitwasdoneface-to-face, now it must be done online, both learning theory and laboratory practice. Online laboratory practice learning will have an impact on student learning outcomes where students will have difficulty achieving learning outcomes because they cannot practice directly with appropriate tools. The study aims to identify the factors that affect the effectiveness of online method laboratory practices in nursing students of the Nursing Department of the Health Polytechnic of the Ministry of Health, JakartaIII.This research is a quantitative study with a cross sectional approach,with Chi- Square analysis, simple and multiple linear regression. The sampling technique used purposive sampling with a total sample of 143 respondents. The questionnaire was developed by researchers and validity and reliability tests have been carried out. The results of this study indicate that students' motivation and learning method scontribute 1.74 times to the success of online laboratory practical learning. It is necessary to readiness of lecturers in making practical learning media online methods and readiness of students to change learning patterns from face to face to online.